Study of effects of negative pressure wound therapy in contaminated wounds - Kundu, Atin; Phuljhele, Satyendra; Wale, Nitin; Gurudatta, Harjot Singh; Agrawal, Vimal (International Journal of Research in Orthopaedics, 2018)
Background: Negative pressure wound therapy is an advanced wound therapy technique that helps in healing the wounds and accelerates granulation tissue as well as wound closure. Methods: Prospective randomized interventional study was done in Dept. of Orthopedics, Dr. BRAM Hospital, Pt. JNM Medical college, Raipur during period from January 2016 to December 2016 involving 25 patients with open fractures up to Gustilo Anderson grade IIIB. All were subjected to this wound technique and response was observed as granulation, size of wound and closure duration. Results: There was up to 10 to 20 mm reduction in wound size with each dressing in half the patients and up to 10 mm in other half of the patients. There was significant reduction in the bacterial growth in all patients and closure was attained in all the subjects after a few therapies. Conclusions: Negative pressure wound therapy is a promising technique to reduce the size of the wound in large wound associated with compound fractures and hasten the healing of wound and its closure.